Faktor - Faktor yang Mempengaruhi Pertumbuhan Deposito Mudharabah pada BUS Periode 2020-2023 - Rifqi, Muhammad; Sulastiningsih, Sulastiningsih (Badan Penerbit Universitas Muria Kudus, 2025)
This research aims to determine the influence return on assets, financing to deposit ratio, profit sharing ratio and inflation on the volume of mudharabah deposits in sharia commercial banks. The sample for this research is Sharia Commercial Banks registered with the OJK for the 2020-2023 period. There were 10 samples in the research method purposive sampling. Data analysis with multiple linear regression using the SPSS application. The research results show The ROA variable partially has a significant and positive effect on the amount of mudharabah deposits in Sharia Commercial Banks. Variable financing to deposit ratio, profit sharing ratio and inflation partially has no effect on the amount of mudharabah deposits in Sharia Commercial Banks. Variable return on asset, financing to deposit ratio, profit sharing ratio and inflation simultaneously influence the amount of mudharabah deposits variable